The use of auxiliary courts by the lek-forming White-bearded Manakin Manacus manacus (Aves, Pipridae) - Cestari, Cesar [UNESP]; Pizo, Marco Aurelio [UNESP] (Springer Heidelberg, 2012)
The White-bearded Manakin is a passerine specially noted for elaborate courtship. Each resident male has a cleaned oval court delimited by saplings in leks. No study mentions the use of more than one court by a territorial male during the breeding season. We report the use of auxiliary courts by males in the lowland forest of southeastern Brazil and discuss its probable function in attracting females for mating. Additionally, we experimentally modified a male's main courts, testing that auxiliary courts serve as alternative display places. Twelve males from four different leks were observed for 145 h. Six males used from one to four auxiliary courts located 1.0 to 8.1 m from their main courts. The males that also used auxiliary courts displayed more than males that used only the main court. Nevertheless, the proportion of female visits per display time indicates that males that used only the main court have greater efficiency in attracting potential mates. Individual males responded differently to the experimental modification of their main courts, but one male avoided the modified court. The use of auxiliary courts may be a strategy adopted mainly by peripheral males to attract females that visit more successful males with central territories on the lek. In the short term, auxiliary courts function as optional display places in cases of loss of the main court. In the long term, the use of auxiliary courts may be involved in the temporal persistence of lek areas.
Keywords: Atlantic Forest; Brazil; Courtship behavior; Sexual competition